Celebrating Evelyn Fox Keller: “The Toronto Statement" - Winther, Rasmus Grønfeldt; Jablonka, Eva; Longo, Giuseppe; Radick, Gregory; Richardson, Sarah S.; Riskin, Jessica; Rupik, Gregory; Soto, Ana M.; Sonnenschein, Carlos; Sultan, Sonia; Vicedo, Marga; Walsh, Denis; et al. (Organisms. Journal of Biological Sciences, 2023)
With much anticipation, in time and spirit, a group of historians and philosophers of biology, and theoretical and experimental biologists, met at the Institute for the History and Philosophy of Science and Technology at the University of Toronto, Canada, on 22 and 23 September 2023, to pay homage to Evelyn Fox Keller for her contributions to theoretical biology. The conference was supported and sponsored by the Department of Philosophy, Institute for the History and Philosophy of Science and Technology, Faculty of Arts and Science (all at University of Toronto), as well as the Social Sciences and Humanities Research Council of Canada. The workshop was an in-person celebration complementing the publication of a volume celebrating her work (Vicedo & Walsh 2020a, 2020b), which includes the following contributions: (Herrington & Jablonka 2020; Longo & Mossio 2020; Radick 2020; Riskin 2020; Soto & Sonnenschein 2020; Walsh 2020). After introductory remarks by Denis Walsh and a short video in which Evelyn Fox Keller thanked us for this homage and wished us well, we learned of her death.